2016
DOI: 10.1093/humrep/dew003
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabonomics for understanding the influence of dormant female genital tuberculosis on metabolism of the human endometrium

Abstract: Government of India, Indian Council of Medical Research. There are no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
3
23
0
1
Order By: Relevance
“…Our earlier study on endometrial tissue NMR metabonomics revealed 21 significantly dysregulated metabolites in women with dormant GTB as compared to controls (Subramani et al 2016a). Interestingly, majority of the metabolites expressed in serum in the present study follow a similar trend as the expression observed in the endometrium of these women.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our earlier study on endometrial tissue NMR metabonomics revealed 21 significantly dysregulated metabolites in women with dormant GTB as compared to controls (Subramani et al 2016a). Interestingly, majority of the metabolites expressed in serum in the present study follow a similar trend as the expression observed in the endometrium of these women.…”
Section: Discussionsupporting
confidence: 78%
“…Levels of L-lysine, lactate, citrate, L-glutamine, L-histidine, L-threonine, L-phenylalanine, and L-tyrosine were found be increased in RSM cases compared to proven fertile women (Supplementary Table 2). The significantly altered metabolites discriminating dormant GTB and RSM cases are presented in Supplementary Table 2. In the present study, we have used Pearson's correlation analysis to identify the association of altered serum metabolites with dysregulated endometrial tissue metabolites in dormant GTB women, reported earlier (Subramani et al 2016a). This analysis shows significant positive correlation among serum metabolites (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Proton nuclear magnetic resonance spectroscopy (1H NMR) is being commonly used for the quantitative assessment of low molecular weight metabolites and functional read-out of cellular phenotypic responses to disease and/or any chemical treatment 14, 16 . In an earlier study, we used 1H NMR metabonomics and could successfully characterize the metabolic profile of the endometrium obtained from women with GTB and healthy controls 17 . This study revealed the possible association of dysregulated energy metabolism and amino acid biosynthesis metabolites with repeated implantation failure in dormant GTB women 4 .…”
Section: Introductionmentioning
confidence: 99%